FLORA POHON DI KAWASAN KAMPUS UNIVERSITAS SAM RATULANGI MANADO - Edwan Tuidano; Marthen T. Lasut; Euis F.S. Pangemanan; Wawan Nurmawan (COCOS, 2016)
ABSRACTThis research has been conducted in the area of Sam Ratulangi University Campus for 2 months, from October to November 2014. This study aims to determine the number of tree species, distribution, and make key identification. The research used the census method. The trees that have been observed have a trunk diameter of over are 10 cm. The morphological observation was made in the roots, trunk, branches, leaves, fruits, and seeds.roots, stems, branches, leaves, flowers, fruits, and seeds. From the observation was found 80 species of trees.Keywords: Flora, Tree, Identification Key.